The history, fungal biodiversity, conservation, and future perspectives for mycology in Egypt - A.M. Abdel-Azeem (IMA Fungus)
Records of Egyptian fungi, including lichenized fungi, are scattered through a wide array of journals, books, and dissertations, but preliminary annotated checklists and compilations are not all readily available. This review documents the known available sources and compiles data for more than 197 years of Egyptian mycology. Species richness is analysed numerically with respect to the systematic position and ecology. Values of relative species richness of different systematic and ecological groups in Egypt compared to values of the same groups worldwide, show that our knowledge of Egyptian fungi is fragmentary, especially for certain systematic and ecological groups such as Agaricales, Glomeromycota, and lichenized, nematode-trapping, entomopathogenic, marine, aquatic and coprophilous fungi, and also yeasts. Certain groups have never been studied in Egypt, such as Trichomycetes and black yeasts. By screening available sources of information, it was possible to delineate 2281 taxa belonging to 755 genera of fungi, including 57 myxomycete species as known from Egypt. Only 105 taxa new to science have been described from Egypt, one belonging to Chytridiomycota, 47 to Ascomycota, 55 to anamorphic fungi and one to Basidiomycota.